High performance self-gating graphene/MoS2 diode enabled by asymmetric contacts. (18th July 2018) - Khan, Muhammad Atif; Rathi, Servin; Lee, Changhee; Kim, Yunseob; Kim, Hanul; Whang, Dongmok; Yun, Sun Jin; Youn, Doo-Hyeb; Watanabe, Kenji; Taniguchi, Takashi; Kim, Gil-Ho
Abstract: A graphene-MoS2 (GM) heterostructure based diode is fabricated using asymmetric contacts to MoS2, as well as an asymmetric top gate (ATG). The GM diode exhibits a rectification ratio of 5 from asymmetric contacts, which is improved to 10 5 after the incorporation of an ATG. This improvement is attributed to the asymmetric modulation of carrier concentration and effective Schottky barrier height (SBH) by the ATG during forward and reverse bias. This is further confirmed from the temperature dependent measurement, where a difference of 0.22 eV is observed between the effective SBH for forward and reverse bias. Moreover, the rectification ratio also depends on carrier concentration in MoS2 and can be varied with the change in temperature as well as back gate voltage. Under laser light illumination, the device demonstrates strong opto-electric response with 100 times improvement in the relative photo current, as well as a responsivity of 1.9 A W −1 and a specific detectivity of 2.4 × 10 10 Jones. These devices can also be implemented using other two dimensional (2D) materials and suggest a promising approach to incorporate diverse 2D materials for future nano-electronics and optoelectronics applications.